A influência exercida pelo amicus curiae nos votos dos ministros do Supremo Tribunal Federal nos acórdãos das ações direta de inconstitucionalidade decididas majoritariamente - Costa, Beatriz Castilho (2012)
The following research project is being presented to the qualification committee of the Fundação Getúlio Vargas Law School of Rio de Janeiro, as a requirement to obtain a Master’s title in the Judiciary System. The object of this research is the decision making procedure of the Supreme Federal Court, with the specific objective of studying the influence exercised by the Court’s external actors in the decision making of its Ministers. In this problematic, the angle chosen was the analysis of the influence exercised by agents that officially participate in the Supreme Federal Court’s procedures acting as amici curiae in the direct actions of unconstitutionality. The dissertation is structured in 3 (three) sections, in the following manner: the first section makes an introduction of the chosen object and the used methodology, as well as the indicators for carrying out a study on the existence or not of the influence of arguments brought by amicus curiae. The second section addresses a brief description of the concentrated control of constitutionality and the role of amicus curiae in the direct action of unconstitutionality. It also encompasses a study made by Damares Medina, the difference of the present work with the latter, and the studied direct actions of constitutionality The third section brings the analysis of the analysis of data found in the 53 (fifty-three) direct actions of unconstitutionality that were herein studied. Lastly, there is this project’s conclusion.